2016
DOI: 10.1177/1558944715614889
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation of Four Internal Fixation Constructs for Scaphoid Fractures

Abstract: All constructs demonstrated similar mechanical properties that may provide sufficient stability for effective clinical use. Given their significantly higher loads-to-failure, a 2.2- or 3-mm screw may be superior to two 1.5-mm screws for fixation of unstable scaphoid fractures. The volar plate did not have superior mechanical characteristics to the compression screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…13,15 Biomechanically, the plate has a similar load to failure (maximum force a structure can resist) to a headless compression screw 27 but was a less stiff construct (or less resistant to deformation), partly due to the thin 0.8-mm profile, although it has more resistance to rotational deformity. 28 This contributes to a different mode of failure; the plate itself failing at the central section in testing where there are no screws.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Biomechanically, the plate has a similar load to failure (maximum force a structure can resist) to a headless compression screw 27 but was a less stiff construct (or less resistant to deformation), partly due to the thin 0.8-mm profile, although it has more resistance to rotational deformity. 28 This contributes to a different mode of failure; the plate itself failing at the central section in testing where there are no screws.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture displacement was quantified by a displacement of the materials testing machine crosshead and has been previously utilized as failure criterion in biomechanical studies assessing mechanical properties of fixed scaphoids. 12,14,17 During cyclic loading, stiffness was calculated at the 1000th cycle or was calculated at the last cycle if the specimen failed prior to completion of the 1000th cycle. Stiffness was quantified by the slope from the linear region of the load-displacement curve.…”
Section: Methodsmentioning
confidence: 99%
“…An a priori power analysis was conducted with α ¼ 0.05 and β ¼ 0.20 based on previous literature pertaining to stiffness and ultimate load of fixed scaphoid fractures 12,14,17 . A sample size of n ¼ 6 was determined for each possible screw length.…”
Section: Methodsmentioning
confidence: 99%
“…There are few biomechanical studies comparing the stability of single versus double screw fixation with conflicting results. [8,9] Similarly, there are only two clinical studies that reported higher union rates in double screw fixation compared to single screw fixation in the current literature. [11,12] We hypothesized that double screw fixation would provide greater rotational stability regarding biomechanical analysis and nonunion rates would be reduced.…”
mentioning
confidence: 92%
“…Biomechanical and clinical studies have shown that newly-developed scaphoid plates provide more stable fixation. [8,9] In addition, Erhart et al [10] have developed new anti-rotational screws particularly designed for scaphoid fractures.…”
mentioning
confidence: 99%